SCHOOL ADAPTATION MONITORING AS A TOOL OF THE PSYCHOLOGICAL SUPPORT SYSTEM IN THE EDUCATIONAL PROCESS - Zhilyaev , A. G. (Modern Psychology, 2019)
Psychological adaptation of children to the learning environment is one of the key characteristics providing an effective "health map" in learners (pupils), as far as this particular feature represents the foundation of successful personal development and education of a child (learner, pupil). Psychological maladjustment is an early and objective predictor of the risk of maladaptive changes in the psychophysiological state of learners. The state of psychological maladaptation is characteristic of an early stage of behavioral disorders in children. Psychological disadaptation may be directly associated with impaired health, both psychological and physical, or learning disability, or may combine all the above aspects. Monitoring represents a simple, available and effective tool for objective dynamic surveillance on the psychological status, it enables identifying negative trends in the mental state of children (learners) in course of the learning process.